Implicit and Explicit Attitudes as Predictors of Gatekeeping, Selective Exposure, and News Sharing: Testing a General Model of Media‐Related Selection. (6th October 2016) - Arendt, Florian; Steindl, Nina; Kümpel, Anna
Abstract : Media‐related selection (MRS) is an umbrella concept for selection processes such as gatekeeping by journalists, selective exposure by audience members, and news sharing by social network site (SNS) users. Importantly, individual attitudes can influence MRS. Previous research on attitude‐based MRS has relied almost exclusively on overtly expressed evaluations (i.e., explicit attitudes) as predictors of selection outcomes. We tested whether automatic affective evaluations (i.e., implicit attitudes) can predict MRS as well. In three studies (gatekeeping, selective exposure, and news sharing), we found that journalists', audience members', and SNS users' implicit and explicit attitudes predicted selection. Thus, attitudes may exert their influence even "under the radar" of conscious awareness.